Traduzioni belles infidèles. Commenti a quelle dei componimenti lubrici di Domenico Tempio - Monzone, Chiel (Italianistica Debreceniensis, 2018)
Belles infidèles is a French expression highlighting a well-known problem in translating from one language to another. This is true especially in the field of literature and particularly in poetry, where the exterior aspects of the words (for example, the harmony of rhymes, the images, the emotional vibrations, the semantic fields, the polysemy, and so on) become substantial and hardly translatable. The essay focuses on some bad translations of some selected verses from the obscene poems by a 18th-century Sicilian dialect poet, Domenico Tempio: they clearly show the translators’ intervention, who took many liberties and betrayed the formulation, the sense and the effect of the original texts. The essay proposes some more faithful translations of them.